2022
DOI: 10.3390/app13010206
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Digital Color Imaging and Machine Learning for the Evaluation of the Effects of Shade Drying and Open-Air Sun Drying on Mint Leaf Quality

Abstract: The objective of this study was to reveal the usefulness of image processing and machine learning for the non-destructive evaluation of the changes in mint leaves caused by two natural drying techniques. The effects of shade drying and open-air sun drying on the ventral side (upper surface) and dorsal side (lower surface) of leaves were compared. Texture parameters were extracted from the digital color images converted to color channels R, G, B, L, a, b, X, Y, and Z. Models based on image features selected for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Drying under the direct sun can lead to losses in the components of the plants (Nurhaslina et al, 2022). Ropelewska et al (2023) reported that when plant leaves are exposed to direct solar radiation, their colours become lighter and their aromas decrease. At the same time, the drying time can make a difference in the amount and variety of the components of the plants.…”
Section: Chemical Compositionmentioning
confidence: 99%
“…Drying under the direct sun can lead to losses in the components of the plants (Nurhaslina et al, 2022). Ropelewska et al (2023) reported that when plant leaves are exposed to direct solar radiation, their colours become lighter and their aromas decrease. At the same time, the drying time can make a difference in the amount and variety of the components of the plants.…”
Section: Chemical Compositionmentioning
confidence: 99%
“…Image analysis and machine learning were successfully applied in previous studies to classify fruits and vegetables [17][18][19] and detect changes in the product quality as a result of different processing, such as drying and fermentation [20][21][22][23]. Furthermore, image features were used to estimate and predict the chemical properties of food products [24,25].…”
Section: Introductionmentioning
confidence: 99%